Acute longitudinal myelitis following Cryptococcus laurentii pneumonia in a patient with systemic lupus erythematosus. (January 2015) - Conti, F; Spinelli, F R; Colafrancesco, S; Truglia, S; Ceccarelli, F; Fattapposta, F; Sorice, M; Capozzi, A; Ferretti, G; Priori, R; Martinelli, F; Pirone, C; et al.
Central nervous system (CNS) involvement in systemic lupus erythematosus (SLE) is reported in about 50% of patients. Among the neuropsychiatric features of SLE, myelopathy, including acute transverse myelitis (ATM) or acute longitudinal myelitis (ALM), represents an uncommon event. A possible vascular aetiology of SLE myelopathies has been hypothesized and it seems to be much more associated to SLE-associated antiphospholipid syndrome (APS). Furthermore, a possible infectious cause of ATM or ALM in healthy subjects has been described. SLE patients are susceptible to infection due to the disease itself or to the immunosuppressive therapy. Cryptococci non-neoformans have been rarely associated to infections in humans. Here we describe the case of a 47-year-old woman with SLE and Sjögren Syndrome who developed an ALM concurrently with a Cryptococcus laurentii pneumonia. The patient was treated with antimycotics, high doses of glucocorticoids and intravenous immunoglobulins with a significant clinical and radiological improvement. As far as we know, this is the first case of Cryptococcus laurentii infection and ALM in a patient with SLE who later developed a seronegative APS. Even though myelopathy may be considered primarily associated to SLE, a possible role of the infection in ALM development cannot be excluded.